NAVIGATING DIGITAL TRANSFORMATION: THE IMPACT OF LEADERSHIP, DIGITAL LITERACY, AND ORGANIZATIONAL CULTURE - Lenita Waty (Program Studi Magister Manajemen Universitas Advent Indonesia, 2024)
Leadership, digital literacy, digital transformation is a critical component of organizations' success. In today's digital world, when the concept of digital literacy is crucial, the role of leadership in building organizational culture is critical. The purpose of this study was to investigate the role that leadership plays in shaping digital transformation through organizational culture and digital literacy. A total of 120 employees were handed questionnaires, of which 108 (or 90%) were useable. The results are: 1). Leadership has a negative and not significant impacts on digital transformation; 2). Leadership has a positive and significant impact on organizational culture; 3). Leadership has a positive and significant impact on digital literacy; 4). Organizational Culture have a positive and significant impact on digital transformation; 5). Digital Literacy have a positive and significant impact on Digital transformation; 6). Leadership has a positive and significant impact on digital transformation through digital literacy; 7). Leadership has a positive and significant impact on digital transformation through organizational culture. The novelty is leadership, digital literacy, and organizational culture is fundamental in the digital transformation process. The interaction between these elements highlights the necessity for leaders to promote technology advancement and cultivate a culture that priorities continuous learning, adaptability, and innovation. This is crucial for driving firms towards attaining digital excellence.